2022
DOI: 10.3390/ijerph19158919
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and Serum Vitamin D Levels: A Systematic Review and Meta-Analysis

Abstract: Vitamin D deficiency and insufficiency are highly prevalent conditions worldwide due to several factors, including poor sun exposure. Shift workers may be exposed to the risk of hypovitaminosis D due to fewer opportunities for sunlight exposure compared to day workers. A systematic review of the PubMed, SCOPUS, and EMBASE databases was conducted according to the Preferred Reporting Items for Systemic Reviews and Meta-Analyses (PRISMA) statement to investigate the effect of shift work on vitamin D levels. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…It indicated that the participants may have relatively regular serum VD concentrations in this study. However, because the optimal 25-OH-D levels are still debated, and the effect of circadian rhythm on serum VD concentration is unclear, the relationship between VD and insomnia requires further exploration ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the participants may have relatively regular serum VD concentrations in this study. However, because the optimal 25-OH-D levels are still debated, and the effect of circadian rhythm on serum VD concentration is unclear, the relationship between VD and insomnia requires further exploration ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Došlo se do zaključka da radnici koji rade u smenama, a naročito noću, imaju niži nivo vitamina D nego radnici koji rade u dnevnoj smeni. Uzrok je taj što su noćni radnici manje izloženi sunčevoj svetlosti u odnosu na radnike koji nemaju smenski rad [38,39]. Pored toga, radnici u noćnoj smeni pokazuju tendenciju ka neredovnom rasporedu obroka, jedenju noću i većem unosu nezdrave hrane, što sve može dovesti do smanjenog unosa vitamina D. Takođe je poznato da radnici koji rade u smenama, a naročito oni koji rade noću imaju tendenciju ka većem BMI (indeksu telesne mase) od opšte populacije, što je faktor koji može dovesti do povećane sekvestracije vitamina D u ma-the limited number of studies, i.e., a small number of studies focusing exclusively on shift workers (as in shift schedule) and the rotating energy intake in the night shift rather than intakes that are more representative of shift work.…”
Section: Ishrana Radnika Koji Rade U Smenamaunclassified
“…Svako prisilno narušavanje normalnih obrazaca spavanja, kao što je rad u smenana, a naročito rad noću, može dovesti do cirkadijalne neusklađenosti i veruje se da je has been concluded that shift workers, especially those who work the night shift, have a lower level of vitamin D compared to those who work the day shift. This is because night shift workers are less exposed to sunlight than those who do not work shifts [38,39]. In addition, night shift workers tend to adopt irregular meal schedules, eat at night, and consume more unhealthy food, which can lead to reduced vitamin D intake.…”
Section: Efekat Rada U Smenama Na Zdravlje Zaposlenihmentioning
confidence: 99%
“…Endogenous vit D is synthesized in the skin from the cholesterol-like precursor (7-dehydrocholesterol) present in epidermal cells by exposure to ultraviolet B (UV-B) from sunlight ( 220 ). Therefore, a lack of UV exposure reduces vit D levels and exacerbates OS in RTECs, which leads to KSD ( 129 , 218 ).…”
Section: Association Between Circadian Rhythm Disturbance and Ksdmentioning
confidence: 99%